The Lineage Differentiation and Dynamic Heterogeneity of Thymic Epithelial Cells During Thymus Organogenesis - Gao, Hanchao; Cao, Mengtao; Deng, Kai; Yang, Yang; Song, Jinqi; Ni, Ming; Xie, Chuntao; Fan, Wenna; Ou, Chunpei; Huang, Dinggen; Lin, Lizhong; Liu, Lixia; et al. (Frontiers in Immunology, 2022)
Although much progress has been made recently in revealing the heterogeneity of the thymic stromal compartments, the molecular programs of cell lineage divergency and temporal dynamics of thymic epithelial cell (TEC) development are largely elusive. Here we constructed a single-cell transcriptional landscape of non-hematopoietic cells from mouse thymus spanning embryonic to adult stages, producing transcriptomes of 30,959 TECs. We resolved the transcriptional heterogeneity of developing TECs, and highlighted the molecular nature of early TEC lineage determination and cortico-medullary thymic epithelial cell lineage divergency. We further characterized the differentiation dynamics of TECs by clarification of molecularly distinct cell states in the thymus developing trajectory. We also identified a population of Bpifa1+ Plet1+ mTECs which was preserved during thymus organogenesis and highly expressed tissue-resident adult stem cell markers. Finally, we highlighted the expression of Aire-dependent tissue restricted antigens mainly in Aire+ Csn2+ mTECs and Spink5+ Dmkn+ mTECs in postnatal thymus. Overall, our data provided a comprehensive characterization of cell lineage differentiation, maturation and temporal dynamics of thymic epithelial cells during thymus organogenesis.